PENGARUH INTERAKSI GURU TERHADAP KREATIVITAS BELAJAR PESERTA DIDIK KELAS X TKJ I DI SMK SWASTA SITI BANUN SIGAMBAL - Paujana, Windiyani; megawati, betti; syawaluddin, fauziahmad (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This research aims to determine the effect of Teacher Interaction on the Learning Creativity Class X TKJ I in SMK Swasta Siti Banun Sigambal, both in Test and Non-Test. The population in this study is grade X TKJ I in SMK Swasta Siti Banun Sigambal, the study time from November to April 2024 which cannot be determined. The determination of the number of samples using the Sugiyono formula with a total of 36 people and the analysis method used is the Test Validity, Test reliable, and hypothesis testing. The result of partial hypothesis testing show that Teacher Interaction has an effect and is significant on Learning Creativity of student in class X TKJ I in SMK Swasta Siti Banun Sigambal. The results of the hypothesis test obtained that the tcount > ttable is 2,960 > 1,688 then H0 is rejected and Ha is accepted, so that there is a significant influence between Teacher Interaction on the Learning Creativity class X TKJ I in SMK Swasta Siti Banun Sigambal.